KONSELING KELOMPOK REALITA UNTUK MENINGKATAN KONSEP DIRI SISWA BROKEN HOME - MAE ENDANG IRIASTUTI (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2022)
Self-concept is the core of personality which plays a very important role in determining and directing the development of personality and behavior. A person with a positive self-concept has a good understanding of his abilities and competencies, on the other hand, a negative self-concept affects negative behavior. Family functioning is one of the most important factors in the formation of self-concept. A harmonious family will form a positive self-concept, a broken home family will lead to a negative self-concept. This study aims to determine the effect of giving group counseling treatment with a reality approach in improving self-concept in broken home students at SMK Negeri 1 Kalasan for the academic year 2021-2022. The research uses a quantitative approach with the correlation method. Determination of the sample using purposive sampling technique. The research subjects were 12 students who had low self-concept from a broken home family, 6 students as the experimental group, and 6 as the control group. The research design used the Kemmis and McTaggart model with 4 stages. The results showed that the students' self-concept scores in the experimental group, from the pre-cycle score of 83.17%, the first cycle score: 89.67%, and the second cycle score: 120%. There was an increase of 15.5% in the first cycle, and 21.33% in the second cycle. Based on the results of the Wilxocon Hypothesis Test of the experimental group, the results of the first cycle of ASYMP.SIG value of 0.028 <0.05, meaning that the hypothesis is accepted, the second cycle of ASYMP.SIG value of 0.027 <0.05, meaning that the hypothesis is accepted. So it can be concluded that the application of Reality Group Counseling is proven to be able to improve the Self-Concept of Broken Home Students at SMK Negeri 1 Kalasan for the academic year 2021-2022. ABSTRAKKonsep diri merupakan inti dari kepribadian yang sangat berperan dalam menentukan dan mengarahkan perkembangan kepribadian dan perilaku. Seseorang dengan konsep diri positif, memiliki pemahaman yang baik tentang kemampuan dan kompetensinya, sebaliknya konsep diri negative mempengaruhi perilaku yang negative. Keberfungsian keluarga merupakan salah satu factor yang sangat penting dalam pembentukan konsep diri. Keluarga harmonis akan membentuk konsep diri positif, keluarga broken home akan menimbulkan konsep diri negative. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian treatment konseling kelompok dengan pendekatan realita dalam meningkatkan konsep diri pada siswa broken home di SMK Negeri 1 Kalasan tahun pelajaran 2021-2022. Penelitian menggunakan pendekatan kuantitatif dengan metode korelasi. Penentuan sampel menggunakan tehnik purposive sampling. Subjek penelitian berjumlah 12 peserta didik yang memiliki konsep diri rendah dari keluarga broken home, 6 peserta didik sebagai kelompok eksperimen, dan 6 sebagai kelompok kontrol. Desain penelitian memakai model Kemmis dan McTaggart dengan 4 tahapan. Hasil penelitian menunjukkan bahwa, nilai konsep diri peserta didik pada kelompok eksperiman, dari skor pra siklus 83,17%, skor siklus I: 89,67%, dan skor siklus II: 120%. Terdapat peningkatan 15,5% pada siklus I, dan 21,33% pada siklus II. Berdasarkan hasil Uji Hipotesis Wilxocon kelompok eksperimen, hasil siklus I nilai ASYMP.SIG 0,028 < 0,05, berarti hipotesis diterima, siklus II nilai ASYMP.SIG 0,027 < 0,05, berarti hipotesis diterima. Maka dapat disimpulkan bahwa Penerapan Konseling Kelompok Realita terbukti dapat Meningkatkan Konsep Diri Siswa Broken Home Di SMK Negeri 1 Kalasan Tahun Pelajaran 2021-2022.